Common statistical errors in logarithmic data of viral load - Suthon Vongsheree (Journal of Associated Medical Sciences, 2018)
Background: The mathematical operation of logarithm data follows the rules of logarithm as the numbers relate to specific meanings. The numbers prior to the decimal are the mantissa or the transformed power of 10 and the numbers after the decimal are the significant numbers of a given numeric data. Such operations result in errors in statistical calculations and lead to erroneous conclusions and eventual miss-interpretation of data.